Effects of Ranolazine on Exercise Capacity, Right Ventricular Indices, and Hemodynamic Characteristics in Pulmonary Arterial Hypertension: A Pilot Study. (1st September 2015) - Khan, Sadiya S.; Cuttica, Michael J.; Beussink‐Nelson, Lauren; Kozyleva, Anastasia; Sanchez, Cynthia; Mkrdichian, Hamorabi; Selvaraj, Senthil; Dematte, Jane E.; Lee, Daniel C.; Shah, Sanjiv J.
Abstract : Ranolazine, a late inward sodium current and fatty acid oxidation inhibitor, may improve right ventricular (RV) function in pulmonary arterial hypertension (PAH); however, the safety and efficacy of ranolazine in humans with PAH is unknown. Therefore, we sought to (1) determine whether ranolazine is safe and well tolerated in PAH and (2) explore ranolazine's effect on symptoms, exercise capacity, RV structure and function, and hemodynamic characteristics. We therefore conducted a 3‐month, prospective, open‐label pilot study involving patients with symptomatic PAH ( n = 11) and echocardiographic evidence of RV dysfunction. We evaluated the safety and tolerability of ranolazine and compared symptoms, exercise capacity, exercise bicycle echocardiographic parameters, and invasive hemodynamic parameters between baseline and 3 months of ranolazine therapy using paired t tests. Of the 11 patients enrolled, one discontinued ranolazine therapy due to a drug‐drug interaction after 3 days of therapy. All 10 of the remaining patients continued therapy for 3 months, and 8 (80%) of 10 completed all study tests. After 3 months, ranolazine administration was safe and associated with improvement in functional class ( P = 0.0013), reduction in RV size ( P = 0.015), improved RV function (improvement in RV strain during exercise at 3 months; P = 0.037), and a trend toward improved exercise time and exercise watts on bicycle echocardiography ( P = 0.06 and 0.01, respectively). Ranolazine was not associated with improvement in invasive hemodynamic parameters. In conclusion, in a pilot study involving PAH, ranolazine therapy was safe and well tolerated, and it resulted in improvement in symptoms and echocardiographic parameters of RV structure and function but did not alter invasive hemodynamic parameters.